Methodological principles of the integral assessment of land efficiency and land organization within the territories of the village councils - Tretiak, A.; Tretiak, V.; Kapinos, N.; Kanivets, O. (Land Management, Cadastre and Land Monitoring, 2020)
In the context of reforming land relations and land system usage individual methodological approaches and systems of natural and economic indicators of land use efficiency assessment require improvement. The current research covers various views and approaches of native scientists to the evaluation of land resource usage with taking into account factorial and result indicators, which differentially influence the formation of elements of land tenure system and land management efficiency. The efficiency of land tenure system and land management is substantiated to be determined by a set of its priority types: environmental, technological, legal, social, economic, and budgetary efficiency and their varieties. A system of criteria and indicators for integrated assessment of land tenure system and land management efficiency level at the local level has been proposed. It includes assessment of environmental, social and economic efficiency which are interrelated and interdependent. It has been confirmed that the development of sustainable and effective methodological bases for land tenure system and land management evaluation is gaining great importance in the context of land market introduction in Ukraine and the abolition of moratorium on agricultural land sale.Keywords. Land tenure system, land management, economic efficiency, environmental efficiency, social efficiency.